PERANAN PEMBIAYAAN PEMBANGUNAN DAN INVESTASI DALAM PEMBANGUNAN DAERAH - Widanta, A.A.B. (INPUT Jurnal Ekonomi dan Sosial, 2008)
The ?nance system in local government during this time still face some constraint. For instance; the unjustice felt bysome local government with the distribution or allocation of center government fund accepted by province. The secondis depending tendency of local government to center. Province of Bali which the contribution its income to the routineand development expenditure above 50 percent is still depend to aid center and abroad. Most of the local income is usedas main resources of the routine expenditure.Meanwhile, The region development in autonomy era is not only focus on economic growth, but also the distributionand increasing the quality of life. Poverty and unemployment are still become the problem which must be given highpriority in region development. This article is aim to identify the condition of development in Province of Bali frommacro aspec (?nance system and investment), the problems of what still be faced, and also things of what paid attentionin the effort to improving the quality of region development.